Correlation of Age and Paracetamol Administration with AEFI Reactions Post Moderna Vaccination at Puskesmas Mojosongo Boyolali - Maslahah, Syah Fillia Nurul; Lestari, Nining; Fauziyah, Nida Faradisa; Soekiswati, Siti (Prosiding University Research Colloquium, 2022)
Many moderna vaccine recipients complain about the presence of AEFI (Adverse Events Following Immunization). Based on CDC data, the frequency of AEFI is higher in the 18-64 year age group. Some studies explain that minor AEFI reactions are managed with paracetamol and subside about 1-2 days after administration of the vaccine. This study aims to determine the relationship between age and administration of paracetamol with AEFI reactions after moderna vaccination at Puskesmas Mojosongo Boyolali. This study used an analytic observational survey research with a cross sectional research design which was carried out with quantitative methods. The data source used is primary data with a g-form questionnaire. This research was conducted at Puskesmas Mojosongo Boyolali, Central Java. The sampling technique in this study was non-random sampling with purposive sampling. The number of respondents is 72 people. The results of the logistic regression test of the relationship between age and AEFI reaction obtained the value of Exp(B) or OR=1.118 (p=0.883). Logistic regression test of the relationship between the administration of paracetamol with the AEFI reaction obtained the value of Exp (B) or OR = 1.949 (p = 0.452). The results of multivariate analysis showed that the variables of age and administration of paracetamol did not have a significant relationship with the reaction of AEFI after moderna vaccination.